World Bank Research Digest, Vol. 3(3) - World Bank (Washington, DC, 2014)
In this issue: banking on politics; focus: what is the evidence on conditional cash transfers? More capital not enough to grow female-owned businesses; no more cutting class? Timing of evaluations and duration of exposure affect estimates of program impact; what drives firm productivity growth? And the challenge of establishing world-class universities.